Potential Value of Matrix Metalloproteinase-13 as a Biomarker for Osteoarthritis - Xin, Xing; Tan, Qizhao; Li, Fang; Chen, Zhongqiang; Zhang, Ke; Li, Feng; Yang, Bin; Xing, Zhili; Zhou, Fang; Tian, Yun; Lv, Yang; Zhu, Tengjiao (Frontiers in Surgery, 2021)
Background: Emerging knowledge has highlighted the role of matrix metalloproteinase (MMP)-13 in osteoarthritis (OA); however, the suitability of MMP-13 as a biomarker for OA remains unclear. Therefore, this study aimed to assess the potential value of MMP-13 as a biomarker for OA. Methods: The study enrolled 51 patients, of which 33 had advanced varus OA and 18 did not have OA. Immunohistochemistry and western blotting analyses were performed to measure MMP-13 activity in the cartilage and subchondral bone of patients with OA. Enzyme-linked immunosorbent assay was used to measure serum MMP-13 levels in patients with or without OA. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used to assess the association between serum MMP-13 levels and clinical symptoms. Furthermore, the association between serum MMP-13 levels and radiological severity of OA was evaluated using the Kellgren–Lawrence (KL) grading system. Finally, we built the proportional odds logistic regression models to evaluate serum MMP-13 levels as a potential predictor for OA. Results: MMP-13 levels were significantly higher in the severe-worn cartilage of the medial tibial plateau than in the relatively intact portion of the lateral cartilage (p < 0.05). This was contrary to the findings for MMP-13 differential expression in the subchondral bone in knee OA (p < 0.05). Patients with OA had significantly higher serum MMP-13 levels compared with patients without OA. Additionally, remarkable associations among serum MMP-13 levels, WOMAC scores, and KL grading scores were found in the end-stage OA. Furthermore, the subsequent analysis suggested that serum MMP-13 level was a significant predictor for OA. Conclusion: MMP-13 is valuable for diagnosing, measuring disease severity, and predicting OA in the advanced period of the disease, suggesting that it has potential possibility as a biomarker for OA. However, the underlying mechanisms and clinical application of MMP-13 as a biomarker for OA require to be further investigated.